Information Technology, Capital Structure and the Nature of Technical Change - Gunnar Eliasson (The Research Institute of Industrial Economics (IUI), 1985)
This paper presents statistical evidence on (1) the importance of 'soft' capital spending items like marketing and R&D investments, and (2) the dominant service content of production in the modern manufacturing firm. It pictures the firm as a dominantly information processing entity that has been gradually shifting its competitive base from process cost efficiency toward a product technology. The paper, hence, argues (3) that during the post-war period technical change has been gradually pivoting in a relatively more (hardware) capital saving direction.
Keywords: L11; L16; L60; 330; R&D investment; firm strategy; technological progress; manufacturing; Informationstechnik; Technischer Fortschritt; Kapitalintensität